Analysis of Corrosion Inhibitor Experiment Design from Tea Extract as Contextual Chemistry Learning - Retno Aliyatul Fikroh*; Faudatul Mukoningah; Shofrina Surya Dewi (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
Experiments are an essential part of teaching chemistry in schools. Experiments in schools involving corrosion sub-materials currently only focus on determining the factors that affect corrosion. There has been no investigation into corrosion prevention using natural materials. The purpose of this research is to identify chemical competency standards in the corrosion sub-material and evaluate the potential of experimental designs for producing iron corrosion inhibitors from tea extract as an alternative experiment in schools. A qualitative description was used in the research, with data collected through literature studies, laboratory experiments, and interviews. According to the study's findings, there was a link between the experimental stages of making iron corrosion inhibitors from tea extract and the corrosion sub-learning material's outcomes. Tea extract corrosion inhibitor can inhibit the best corrosion rate of 4.10-5 g/cm2.day at 20% inhibitor concentration with 90% inhibition efficiency. Based on an analysis of the financial aspect, it was stated that the experimental design of iron corrosion inhibitors from tea extract required a relatively low cost. In contrast, from the human resource readiness aspect, it was stated that this experimental design could be used as an alternative to chemical experiments based contextually on the corrosion sub-material in schools.